Embarrassed Radiofrequency Catheter Ablation of Supraventricular Tachycardia in Pectus Excavatum - Gahyun Lee; Ji-Eun Ban (The Ewha Medical Journal)
A 16-year-old patient with pectus excavatum visited our hospital because of palpitation. He underwent first Nuss operations at the age of 3. When he was 13 years old, the slow-fast type atrioventricular nodal reentrant tachycardia was documented during electrophysiology study. However, the catheter ablation was not conducted because of recurrent atrial fibrillation during procedure. At that time, second Nuss operation was performed due to progressive chest wall deformity. And then, atrioventricular nodal reentrant tachycardia was successfully treated by radiofrequency catheter ablation at the higher position than usual slow pathway zone under the modified fluoroscopic view with the cranial angle although distorted right atrial geometry and radiographic obstacle of Nuss operation bar. The concern about abnormal cardiac and electrical anatomy, and the accurate and modified procedure technique are essential in patients with pectus excavatum. (Ewha Med J 2022;45(3):e6)